2 - The African Union and Conflict Management - Albert, Isaac Olawale (Africa Development, 2007)
This paper reflects on the ability of the African Union (AU) to implement its conflict management mechanism. The response of the AU to the ‘military coup’ in Togo and its mission in Sudan are used as case studies. The emerging picture is that African leaders are now alive to their responsibilities for making, building and keeping peace in Africa. African leaders know that the days of non-interfer- ence and expecting the rest of the world to resolve conflict situations created by them are over. The AU would, however, achieve better results if the member states are more committed to removing the problems faced by the organisation. The most salient include the poor commitment of some African leaders to posi- tive peace, the regional organisation is still as under funded as the former OAU, and the problem of weak national armies in some member states compromises efficiency of peace support operations.